A Collaboration-Based Model of Work Motivation and Role Ambiguity in Public Organizations. Issue 3 (2nd July 2016) - Campbell, Jesse W.
ABSTRACT: Intra-organizational collaboration has long been recognized as a potential source of improved performance for public organizations. In collaborative organizations, frontline employees can leverage interpersonal networks to access a broad pool of expertise and experience, resources that can then be used to overcome obstacles or take advantage of emergent opportunities. Given this link to goals, information flow, and empowerment, this study examines how intra-organizational collaboration affects work motivation, and posits that reduced role ambiguity plays a key role in this relationship. Building on previous literature, three species of collaboration—vertical interpersonal, horizontal interpersonal, and inter–work unit collaboration—are discussed. Using data from a large survey of American federal employees, structural equation modeling is used to test the hypothesized model. The results of the analysis suggest that reduced role ambiguity functions as an important mediating mechanism linking intra-organizational collaboration to work motivation. The implications of these findings for public management are discussed.